Sero-epidemiology of brucellosis in small ruminants on rangeland in northern Mexico - Mellado, M; Almanza, A; Mellado, J; García, JE; Macías-Cruz, U; Avendaño-Reyes, L (Journal of the Hellenic Veterinary Medical Society, 2023)
The seroprevalence of Brucella antibodies in serum of goats and sheep reared on semi-arid pastoral systems of northeastern Mexico was assessed. Additionally, species, gender, and predominant breed were evaluated as risk factors for seropositivity to brucellosis. Data were from 375 flocks of goats or co-mingled goats and sheep. Serum samples from 11001 goats and 4741 sheep collected between 2016 and 2019 were analyzed with the brucellosis card test. The disease affected 12% of flocks. The overall prevalence of brucellosis seropositivity in goats and sheep were estimated at 2.1% (95% CI = 1.78-2.31) and 0.8% (95% CI = 0.58-1.10), respectively. Brucellosis seropositivity was two times more likely (p < 0.01) in goats than sheep. The risk of seropositivity to brucellosis for goats and sheep was 2.3 and 3.2 times higher (p < 0.01) in females than males. Toggenburg goats were more likely (p < 0.01) to be seropositive to brucellosis than all other breeds of goats, whereas criollo sheep were more likely to be seropositive to brucellosis compared to hair sheep composite breeds. The current study revealed that, despite the absence of Brucella vaccination, brucellosis is not widely distributed in the study area. Also of all animals screened, seropositivity to Brucella infection was highest in Toggenburg when compared to other dairy and meat breeds; Criollo sheep also presented the highest seropositivity to brucellosis compared to hair sheep composite breeds. Finally, females compared to males had increased odds of testing positive for brucellosis.